PERENCANAAN PEMBANGUNAN BERBASIS E-PLANNING DI BAPPEDA PROVINSI DIY - Jamaluddin, Sholeh -; -, Kushandajani -; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2024)
Innovation and the use of information and communication technology are requirements to make planning go in a better direction. The Government of Yogyakarta Special Region in terms of development planning applies the principle of e-government by implementing electronic-based planning. This innovation is realized with supporting applications in the form of JogjaPlan and SIPD which help the planning process in the region. This research aims to find out and analyze the obstacles and strategies in the implementation of the E-Planning system at the Regional Planning and Development Agency of Yogyakarta Province. This research uses descriptive qualitative methods and data collection techniques through interviews and observations. The results of this study indicate that the implementation of e-planning has benefits in the form of maintaining the consistency of development planning, making the planning process run quickly and on time, integrating planning databases, and opening opportunities for community participation. But on the other hand, there are still obstacles in the form of employee shifts that can have an impact on employee abilities, the level of community participation through JogjaPlan is still minimal, there is no maximum integration between JogjaPlan and SIPD, the responsiveness of the application server is not stable, and the utilization of Geographic Information Systems (GIS) is not maximized. With these obstacles, strategies can be taken in the form of increasing employee capacity building through competency training, increasing socialization in the community, strengthening application servers, and integrating data between JogjaPlan and SIPD applications